LANGUAGE CONVERSION OF THE WRITERS WITH CENTRAL EUROPEAN BACKGROUND AS A COMMUNIATION STRATEGY WITH THE MAINSTREAM LITERATURE - Czaplińska, Joanna (Porównania, 2014)
The article deals with the problem of presenting the experience of living in a totalitarian or socialist state, based on the novels by three authors who write in a language other than the mother tongue: coming from Slovakia Irena Brežná and the Czech Republik Libuše Moníková whose work was written in German, and living in Canada and writing in English Eva Stachniak. The analysis was made by means of the novels Verklachte Nacht by Moníková, Die beste aller Welten, Roman by Brežná and Necessary Lies by Stachniak. In their works, the authors take a variety of stategies to provide information about life behind the iron curtain, from the purely journalistic information, information woven into the story, to the stream of consciousness, showing how propaganda shapes thinking.